LEGAL PROTECTION OF TRANSPORTATION SERVICE PERFORMERS FOR GOVERNMENT PRICING POLICIES ON OIL FUEL ( BBM ) - Sudiyana, Sudiyana (Kajian Hasil Penelitian Hukum, 2023)
The purpose of this research is to identify and analyze the legal protection of transportation service providers due to the government's policy of fixing fuel prices.This study uses a type of normative.Research results describe all the materials regarding the problems raised by legal protection for transportation service actors over the government's policy of fixing prices for fuel oil (BBM ).Legal protection for perpetrators of transportation services is based on the following provisions; a. Law Number 22 of 2009 concerning Road Traffic and Transportation b. Law Number. 8 of 1999 concerning Consumer Protection c. Law of the Republic of Indonesia Number 22 of 2001 concerning Oil and Natural Gas Legal protection for transportation business actors. Several factors become obstacles to legal protection for transportation service actors, government policy in setting the price of fuel oil (BBM),